(untitled) (Journal of the College of Basic Education, 2022)
This research is concerned with studying the problems that occurred between Afghanistan and Iran for the period between (1929-1973) regarding the sharing of water in the border Harmand River, in an important era in the history of international relations, as the region witnessed in that era major political transformations.